The Effects of Ear Acupressure on Back Pain after Coronary Angiography: A Randomized Controlled Trial - Seyyed Abolfazl Vagharseyyedin; Mojgan Kardan; Hossein Rahimi; Hamidreza BahramiTaghanaki; Nahid Azdaki (Tehran University of Medical Sciences, 2022)
Back pain is a common complaint seen in patients after coronary angiography. This study investigated the efficacy of ear acupressure for reduction of back pain in patients after coronary angiography. In this trial, 120 patients recruited from a post-angiography ward were allocated to an ear acupressure or a control group. Pain assessment in intervention group was performed immediately after participants entered post- coronary angiography ward (T0), twenty minutes after entering the ward (T1), and two, four, and six hours after the intervention (T2-T4). Pain in control group was assessed at the times similar to intervention group. Data were analyzed using the SPSS software (v. 19) by Chi-square, Fisher's exact, independent t tests, Friedman test, Wilcoxon signed-rank, and Mann-Whitney U test. Final data analysis was done on the data gathered from 58 participants in the control group and 59 in the ear acupressure group. The pain intensity at T1-T4 for patients in the control group was significantly higher than T0 (P < 0.001), while patients in the ear acupressure group reported that pain intensity at T2-T4 was significantly higher than T0 for them (P < 0.001). Only at T1 and T2, pain intensity in the ear acupressure group was significantly less compared to the control group (P < 0.05). Ear acupressure in this study was effective to some extent in reducing back pain after coronary angiography. Future studies can be designed to examine the effects of ear acupressure using different ear acupressure points on the back pain after coronary angiography.